2018
DOI: 10.1371/journal.pone.0204613
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physicians’ attitude and reported prescribing behavior for chronic low back pain: An exploratory cross-sectional study

Abstract: ObjectiveRecent guidelines for chronic or recurrent low back pain recommend non-pharmacologic treatments as first-line options. The objective of this study was thus to explore the perceived usefulness of several conventional and complementary medicine treatments for chronic or recurrent low back pain by primary care physicians and their reported prescribing behavior.DesignAn exploratory cross-sectional study.Setting and participantsPrimary care physicians of the French-speaking part of Switzerland.Main outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The sociodemographic profile of the study participants revealed that the majority were young women who had graduated less than 5 years earlier, mainly from public universities, and whose current area of activity was public PHC. In this context, in a study conducted with primary care physicians in Switzerland, it was found that women and young people are more likely to recommend integrative practices, 8 a finding compatible with the profile raised by this study. It was also verified that 81.8% of the respondents underwent the Introduction to Acupuncture course while attending medical residency in family medicine.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The sociodemographic profile of the study participants revealed that the majority were young women who had graduated less than 5 years earlier, mainly from public universities, and whose current area of activity was public PHC. In this context, in a study conducted with primary care physicians in Switzerland, it was found that women and young people are more likely to recommend integrative practices, 8 a finding compatible with the profile raised by this study. It was also verified that 81.8% of the respondents underwent the Introduction to Acupuncture course while attending medical residency in family medicine.…”
Section: Discussionsupporting
confidence: 87%
“…Few studies have investigated the profile of medical doctors that underwent acupuncture training or provided follow-up data of the repercussion of acupuncture in a physician’s clinical practice. 812 There is a scarcity of literature that addresses the implementation of acupuncture in the context of primary care 13 or that describes experiences of complementary acupuncture education for PHC physicians and FCM residents. 14 Therefore, the aim of this study was to analyze the profile of acupuncture use by physicians who underwent the Introduction to Acupuncture course offered in the public health system of the city of Florianópolis, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of skill sets of recruited healthcare professionals, physiotherapists, psychologists and nurses were the most common intervention facilitators, potentially indicative of a need to focus on education around physical activity, mental health (notably, cognitive behavioural strategies) and general lifestyle changes. Communication between participants and these three types of healthcare professionals is likely to reshape beliefs and behaviour of people with chronic pain, an outcome identified in previous research involving various healthcare professionals and health conditions such as low back pain and palliative care [28, 7780].…”
Section: Discussionmentioning
confidence: 99%
“…While the mention of ‘acupuncture’ can connote ‘complementary’ or ‘alternative’ medicine to some PCPs, others may already view acupuncture as part of usual care for LBP. 21 PCPs who have used acupuncture themselves are more likely to recommend acupuncture to their patients, 22 so it may be more important to disseminate information to those who have no personal experience with acupuncture. It is unclear whether communicating acupuncture as an “alternative” is detrimental to the adoption of acupuncture by PCPs and other stakeholders, but could be tested.…”
Section: Acupuncture For Lbp In Younger Adultsmentioning
confidence: 99%